Eksistensi Tuhan Saat Wabah Covid 19 Melanda - Albertus Bernando Agung Hamonangan Situmorang (Sekolah Tinggi Filsafat Seminari Pineleng, 2022)
The essay presents a philosophical discussion on the question of God’s existence during the time of covid-19. Methodologically it is a qualitative study. The author develops his argument by studying some relevant literature on the topics. The literature study focuses on some concepts of western and easter philosophy regarding the root of human suffering. The result shows that the fact of suffering does not derive from God, but from the free will of human beings. In Buddhism suffering is thought of as dukkha that exists from the very beginning of human life. To be free from this dukkha, man must live the so-called liberating paths of truth. In the western concept, suffering has nothing to do with God, because God himself did not create or will the suffering. God only wants to be consistent with His creation, namely to give full freedom to the creatures.